Eksplorasi Etnomatika pada Masyarakat Petani Padi di Desa Padang Cekur - Oka Sumanto; Revi Yuliani; Gita Lavenia; Resti Komala Sari (Yayasan Darussalam Bengkulu, 2023)
This research problem is based on the question of how the ethnomathematics of rice farmers in Padang Cekur village. This study aims to explore the mathematical aspects related to the rice farming community in Padang Cekur village and also to identify them as one of the many learning resources in mathematics schools. The method used in this study is descriptive research. The techniques applied are interviews and documentation. The subjects are rice farmers. The results show that: There are mathematical aspects in the rice farming community in Padang Cekur village, they measure, discover, design, and explain aspects. Mathematical aspects found in the community can be categorized as elementary school mathematics and junior high school students. This discovery can help students to represent the knowledge they have obtained from class to be applied in everyday life. The conclusion that can be drawn is that there is ethnomathematics in the rice farming community in Padang Cekur village